INDICATORS OF NONSPECIFIC RESISTANCE OF EARLINGS CARP WITH INVASION BY ЕCTOPARASITES - Лобойко, Ю. В. (Scientific Progress & Innovations, 2013)
The data on lyzocymic and bactericidal activity of serum and blood phagocytic activity of neutrophils by different intensity of infestation by ectoparasites. The decrease lyzocymic, bactericidal and phagocytic activity of carp serum by lesions ectoparasites Lernaea cyprinacea and Dactylogyrus vastator compared with clinically healthy fish.